2013
DOI: 10.1103/physrevb.88.014431
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated magnetization reversal in bulk BiFe0.5Mn0.5O3

Abstract: We report on the synthesis and characterization of BiFe0.5Mn0.5O3, a potential type-I multiferroic compound displaying temperature induced magnetization reversal. Bulk samples were obtained by means of solid state reaction carried out under the application of hydrostatic pressure at 6 GPa and 1100{\deg}C. The crystal structure is an highly distorted perovskite with no cation order on the B site, where, besides a complex scheme of tilt and rotations of the TM-O6 octahedra, large off-centering of the bismuth ion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…properties [10][11][12][13][16][17][18][19][20][21][22][23][24][25]. However, experimentally it is hard to achieve the exactly ordered BFMO supercell structure.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…properties [10][11][12][13][16][17][18][19][20][21][22][23][24][25]. However, experimentally it is hard to achieve the exactly ordered BFMO supercell structure.…”
Section: +mentioning
confidence: 99%
“…However, experimentally it is hard to achieve the exactly ordered BFMO supercell structure. At present, only disordered BFMO bulk and films, in which Fe and Mn ions are randomly distributed at B sites, have been synthesized, and no convincing experimental evidence for Fe-Mn ordering along [111] direction is found [13,[16][17][18][19]. In addition, recent neutron diffraction experiment further confirmed Fe and Mn disordering at B sites at RT in BFMO epitaxial films [21].…”
Section: +mentioning
confidence: 99%
“…Consequently, the standard procedure applied to describe hyperfine field distribution 24 and the scheme adopted in ref. 25 can be used in the present case. In order to limit the total number of base functions, we introduced only two kinds of clusters and four sub-spectra for each of them, obtaining eight base sub-spectra in total.…”
Section: Mössbauermentioning
confidence: 99%
“…The magnetic pole inversion (or magnetic reversal) is defined as the crossover of DC magnetization from positive to negative as a function of temperature in a magnetically ordered system . Even though this phenomenon is rare, recent studies have revealed the tunable and multiple magnetic pole inversions in multiferroics BiFeO 3 (denoted as BFO) . Due to its high ferroelectric Curie temperature (1103 K) and antiferromagnetic Néel temperature (643 K), BFO is one of the most promising single‐phase multiferroics and has attracted a lot of attention .…”
Section: Introductionmentioning
confidence: 99%
“…1 Even though this phenomenon is rare, recent studies have revealed the tunable and multiple magnetic pole inversions in multiferroics BiFeO 3 (denoted as BFO). 2,3 Due to its high ferroelectric Curie temperature (1103 K) and antiferromagnetic Néel temperature (643 K), BFO is one of the most promising single-phase multiferroics and has attracted a lot of attention. [4][5][6][7] Notably, the intrinsic defects of oxygen vacancies in BFO can significantly impact its properties, 8 such as changing the fatigue behavior, remnant polarization 9,10 and thermal conductivity, 11 increasing the leakage current, 12,13 and inducing dielectric relaxation and magnetodielectric, 14 weak ferromagnetism, 15,16 and electrochromism.…”
Section: Introductionmentioning
confidence: 99%